TOURISM ATTRACTIONS DEVELOPMENT THROUGH THE TAPPING ACTIVITIES OF LONTAR TREE IN TOURIST ATTRACTION LASIANA BEACH KUPANG CITY - Eky, Feny Susana; Saragi, Rulli (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2020)
Lasiana Beach, Kupang City is one of the leading tourist attraction in Kupang city because it has a strategic location, is easy to reach and holds cultural potential that attractive and educative. However, the development of this tourist attraction has not been carried out optimally, especially on the elements of attraction which are the main elements of a tourist attraction. The purpose of this study is to develop palm tree tapping activities as an attractive and educative tourist attraction in tourist attraction Lasiana beach. The methodology used is a qualitative research method. The results showed that palm tree tapping activity as a tourist attraction in tourist attraction Lasiana beach can be packaged into a tourist attraction that fulfills three basic tourist elements, namely can be seen (something to see), can be done (something to do), and can be purchased (something to buy).